Effects of Extra-Curricular Activities on the Academic Performance of Intermediate Pupils - Vital, Rosewell Ann (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of extra-curricular activities on the academic performance of intermediate pupils in selected public elementary schools in the Angono District, Division of Rizal during the School Year 2025–2026. The research aimed to determine the extent to which participation in extra-curricular activities influences pupils’ learning engagement, task accomplishment, performance in written examinations, and assignments. A descriptive survey research design was employed to gather data from the respondents. The participants consisted of seventy-seven (77) intermediate teachers, representing one hundred percent of the teacher population, and two hundred (200) pupils who were actively participating in various extra-curricular activities. The teacher-respondents were described in terms of age, sex, civil status, length of service, position title, educational attainment, and in-service trainings attended. Meanwhile, the pupil-respondents were profiled based on age, sex, sibling position, number of children in the family, monthly family income, parents’ educational attainment, parents’ occupation, and the extra-curricular activities in which they participated.Data were collected using a researcher-made questionnaire-checklist designed to measure the perceived effects of extra-curricular activities on pupils’ academic performance. Documentary analysis was also conducted using the pupils’ first quarter grades from School Form 9 to determine their level of academic performance. The findings revealed that extra-curricular activities affect the academic performance of intermediate pupils to a high extent, particularly in terms of learning engagement, task accomplishment, and performance in written examinations and assignments. Both teachers and pupils shared similar perceptions regarding the positive effects of these activities. The pupils’ academic performance was rated Very Satisfactory, with a mean grade of 86.42. Moreover, the results showed a significant relationship between pupils’ involvement in extra-curricular activities and their academic performance.The study concluded that participation in extra-curricular activities contributes positively to pupils’ engagement and academic achievement. Strengthening school-based extra-curricular programs and aligning them with academic objectives are recommended to support pupils’ holistic development and improve learning outcomes.